Alavancagem como instrumento de estratégia operacional: o caso da obra de construção da nova sede da Assembléia Legislativa do Estado do Maranhão - Parente, Samária Uchôa de Menezes (2006)
Due to high competitiveness in the current market, those companies which are deeply aware of their financial results have some competitive advantages, and based on that information, their managers can take decisions aiming at the maximization of their profit. Therefore, this research deals with the leverage as an operational strategy tool, for this it presents a study on a civil construction. In this field of activity, workmanship is a huge insume and the employees work overtime increasing the profits of the company. The main goal of this research is to demonstrate how the operational leverage can be used as an operational strategy tool in this context. It is a descriptive and applied research as to its goals and bibliographical, documentary and a field one as to the way it was performed. It took place during and at the construction of the new head office of the Legislative Assembly of Maranhão, which was carried out by the Petra Construção Ltda company in São Luís city.